Integrating views of properties in models of unit manufacturing processes. Issue 9 (1st September 2016) - Denno, Peter; Kim, Duck Bong
Abstract : This paper investigates the potential advantages and difficulties of integrating predictive model equations in models of unit manufacturing processes. The method described uses metamodels and semantic web technology to relate equations, as objects, to downstream activities. The potential advantages of this include enhanced knowledge refinement and reuse, traceability, model verification and agility in production activities. In an example usage, the authors apply the method to the development and downstream usage of predictive models of a selective laser sintering process. Use of equations as objects enables linking them with supporting evidence, property definitions and dimensions in an engineering notebook paradigm. Model-based interpretation of the equations enables composition in trade studies and mapping to downstream process parameter optimisation.